Designing An Accounting Information System Based On Microsoft Access And Internal Control At Pt Tri Wira Buana - Fiona Fiona; Androni Susanto (ConCEPt - Conference on Community Engagement Project, 2023)
PT Tri Wira Buana is a company engaged in the property and housing developer sector which is still doing manual recording, causing slow data processing and ineffective preparation of financial reports. Therefore, this community service activity aims to design an easy and user friendly and computerized accounting information system based on Microsoft Access. The methods used are interviews, observation, and documentation. The result of the service is a Microsoft Access system consisting of information namely customer, supplier, inventory, and transaction forms consisting of sales, purchase, payment, receipt, and disbursement forms. The reporting in the Microsoft Access system are financial reports in the forms consisting of ledgers, trial balance, income statement, changes in capital, financial position, sales, and purchases. This system already integrated with each other and can generate reports per period. The implementation of the system has been conducting well, helping the reporting and improve the quality of bookkeeping at PT Tri Wira Buana. This system can also use as a reference and adopted for similar industries.